Oxygen harvesting from carbon dioxide: simultaneous epoxidation and CO formation. Issue 40 (20th September 2021) - Xu, Han; Shaban, Muhammad; Wang, Sui; Alkayal, Anas; Liu, Dingxin; Kong, Michael G.; Plasser, Felix; Buckley, Benjamin R.; Iza, Felipe
Abstract : Selective formation of atomic oxygen to form epoxides in a waste free process is reported. Simultaneously generating carbon monoxide from carbon dioxide for further use. Abstract : Due to increasing concentrations in the atmosphere, carbon dioxide has, in recent times, been targeted for utilisation (Carbon Capture Utilisation and Storage, CCUS). In particular, the production of CO from CO2 has been an area of intense interest, particularly since the CO can be utilized in Fischer–Tropsch synthesis. Herein we report that CO2 can also be used as a source of atomic oxygen that is efficiently harvested and used as a waste-free terminal oxidant for the oxidation of alkenes to epoxides. Simultaneously, the process yields CO. Utilization of the atomic oxygen does not only generate a valuable product, but also prevents the recombination of O and CO, thus increasing the yield of CO for possible application in the synthesis of higher-order hydrocarbons.